Convergent Loss of Prothoracicotropic Hormone, A Canonical Regulator of Development, in Social Bee Evolution - Costa, Claudinéia P.; Okamoto, Naoki; Orr, Michael; Yamanaka, Naoki; Woodard, S. Hollis (Frontiers in Physiology, 2022)
The evolution of insect sociality has repeatedly involved changes in developmental events and their timing. Here, we propose the hypothesis that loss of a canonical regulator of moulting and metamorphosis, prothoracicotropic hormone (PTTH), and its receptor, Torso, is associated with the evolution of sociality in bees. Specifically, we posit that the increasing importance of social influences on early developmental timing in social bees has led to their decreased reliance on PTTH, which connects developmental timing with abiotic cues in solitary insects. At present, the evidence to support this hypothesis includes the absence of genes encoding PTTH and Torso from all fully-sequenced social bee genomes and its presence in all available genomes of solitary bees. Based on the bee phylogeny, the most parsimonious reconstruction of evolutionary events is that this hormone and its receptor have been lost multiple times, across independently social bee lineages. These gene losses shed light on possible molecular and cellular mechanisms that underlie social evolution. We outline the available evidence for our hypothesis, then contextualize it in light of what is known about developmental cues in social and solitary bees, and the multiple precedences of major developmental changes in social insects.